Competition and Poverty - Begazo, Tania; Nyman, Sara (World Bank, Washington, DC, 2016)
A literature review shows competition policy reforms can deliver benefits for the poorest households and improve income distribution. A lack of competition in food markets hurts the poorest households the most. Competition in input markets and between buyers helps farmers and small businesses. And more competitive markets bolster job growth over the longer term. More research is needed, however, to better understand the impact of competition reforms and antitrust enforcement on poverty and shared prosperity.